(3GdWH GdfHhjs - (3CMeO Hf YHO Gddg Hf CMeO GdCUHgGfj, CHh fYje, J (B430 (3g` s
(3ChdgG (B:s
(3GdMeO dUGfY GdCQhGM hGdCLSGe hOGaY GdChUGH hGdCSbGe, GdefYe Ydi eaJbQjg HGdYGajI ef YhGQV GddjGdi hGdCjGe s
(3BNQgG (B:s
(3SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd(B: (3ef bJd YUahQkG YHKkG YL (B" s
(3Cdag Ydi ZQGQ cJGH GdWH dCHi HcQ CMeO Hf eMeO Hf ESMGb GdSfj GdOjfhQjs
(3QhGjI jhSa Hf Ndjd Hf YHOGddg GdOeTbjs
(3GfXQ GjVG agQS GdWH Qbe (B163s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B282s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B151 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B271 s
Keywords: (3GdWHs